2004
DOI: 10.1186/1472-6874-4-s1-s26
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Bacterial STIs in Canada

Abstract: Health Issue: The incidence of bacterial sexually transmitted infections (STIs) is rising in Canada. If these curable infections were prevented and treated, serious long-term sequelae including infertility, and associated treatment costs, could be dramatically reduced. STIs pose a greater risk to women than men in many ways, and further gender differences exist in screening and diagnosis.Key Findings: Reported incidence rates of chlamydia, gonorrhea, and infectious syphilis declined until 1997, when the trend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…Our study is the first to compare the STI screening results of an infertile male population with the general population of the country of study. The findings of our study demonstrate that when infertile Canadian men are screened for CT and NG in the tertiary care setting, the positive rate is statistically significantly lower than that of the general population, even when the reported rates in the general population are an underestimate (33). There are limitations in comparing a largely unscreened, symptomatic general Canadian population with a screened male infertility population, but this comparison is important to note as it reiterates that infertile men presenting to a tertiary infertility clinic are at extremely low risk for CT/NG in the Canadian context.…”
Section: Discussionmentioning
confidence: 55%
“…Our study is the first to compare the STI screening results of an infertile male population with the general population of the country of study. The findings of our study demonstrate that when infertile Canadian men are screened for CT and NG in the tertiary care setting, the positive rate is statistically significantly lower than that of the general population, even when the reported rates in the general population are an underestimate (33). There are limitations in comparing a largely unscreened, symptomatic general Canadian population with a screened male infertility population, but this comparison is important to note as it reiterates that infertile men presenting to a tertiary infertility clinic are at extremely low risk for CT/NG in the Canadian context.…”
Section: Discussionmentioning
confidence: 55%
“…38 Pelvic inflammatory disease is responsible for 15% of all infertility. 39 The increased risk is due not only to the greater mucosal surface area present in women but also to the exposed squamocolumnar epithelium of the cervical os in female adolescents, which is less resistant to these pathogens. 39 In vivo studies 20 of topical microbicides against vaginal chlamydia found promising results of significantly reduced infection.…”
Section: Genital Discharge Diseases: Gonorrhea Chlamydia and Trichomentioning
confidence: 99%
“…However, healthy sexuality campaigns aimed at reducing HIV infection developed in the early years of the epidemic were developed ostensibly by and for gay men, more recently for "men who have sex with men," and were largely based on risk group categories (Centers of Disease Control 2006;Connell 2001;Murphy, Rotherman-Borus, and Reid 1998;Rotherman-Borus, Marelich, and Srinevasan 1999). As such, HIV prevention programs and services did not address the gender-based differences in sexual risk behaviours across all sectors of the population, particularly young heterosexuals in Canada (Canadian Public Health Association 2001;Gatali and Archibald 2004;Planned Parenthood Federation of Canada 2001;Wong et al 2004). …”
Section: Introductionmentioning
confidence: 99%